2013
DOI: 10.1002/acn3.25
|View full text |Cite
|
Sign up to set email alerts
|

Progressing small vessel pontine infarction includes different etiologies

Abstract: BackgroundThe aim of this study was to investigate the clinical features of progressing stroke of pontine infarction as small vessel disease.MethodsEnrolled 38 acute pontine infarctions were confirmed by magnetic resonance imaging and magnetic resonance angiography at the first and seventh days. Ten patients (26.3%) presented progression (NIH Stroke Scale ≥2 increase within 72 h).ResultsProgressing patients showed no relation to the size and the distribution of lesion. Expansion of ischemic lesion showed corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…In addition, we also analyzed the correlation between different location of cerebral infarction and clinical progression of cerebral infarction in this study. The results showed that progressive cerebral infarction of perforating artery was mainly distributed in the areas of the para -body of lateral ventricle and pons, which was consistent with previous studies ( Li et al, 2020 , Nakase et al, 2014 ). The reason is that the supplying artery of the para -body of lateral ventricle is the superficial branch artery of the middle cerebral artery, such as the lenticulo-striate artery and the anterior choroid artery.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we also analyzed the correlation between different location of cerebral infarction and clinical progression of cerebral infarction in this study. The results showed that progressive cerebral infarction of perforating artery was mainly distributed in the areas of the para -body of lateral ventricle and pons, which was consistent with previous studies ( Li et al, 2020 , Nakase et al, 2014 ). The reason is that the supplying artery of the para -body of lateral ventricle is the superficial branch artery of the middle cerebral artery, such as the lenticulo-striate artery and the anterior choroid artery.…”
Section: Discussionsupporting
confidence: 92%
“…However, Multiple logistic regression results showed that the OR of BABD was much higher than the OR of infarct volume in our study,So We speculated that subtype-BABD has a greater impact on the occurrence of END. Interestingly, another study [ 8 ] suggested that END was not related to the size of either infarct; however, its sample size was relatively small ( n = 38), the expansion of ischemic lesions was not correlated with END, and the actual lesion size was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [ 3 , 7 ], END was reported to be related to the topographic location of the pontine infarction. However, another study showed that END was independent of the location and was not correlated with the size of the infarct [ 8 ]. Recently, the infarct size rather than topographic location of pontine infarction was suggested to be a possible predictor of END [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tegmental infarction usually represents SAD, and most unisolated pontine infarctions were caused by SAD in our study. Bilateral pontine infarction indicates severe neurological dysfunction and is related to poor outcomes [17, 18]. Claudio et al showed that 11% of isolated pontine infarctions were bilateral ventral infarctions [8].…”
Section: Discussionmentioning
confidence: 99%